2023
DOI: 10.3991/ijet.v18i17.42215
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT in Ukrainian Education: Problems and Prospects

Svitlana Fiialka,
Zoia Kornieva,
Tamara Honcharuk

Abstract: This paper highlights the impact of artificial intelligence (AI) and text-generating models such as ChatGPT (GPT-Generative Pretrained Transformer) on Ukrainian education. It has been found that the introduction of this tool is both beneficial and problematic. On the one hand, it saves time for the information search, facilitates the research process for both teachers and students through proposing ideas, and creates education-related content that emulates human writing. On the other hand, ChatGPT sometimes ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Abu Khurma et al ( 2023) examined ChatGPT's use in UAE education, highlighting its benefits and drawbacks and providing ethical recommendations. Ukrainian higher education also demonstrated the impact of ChatGPT, revealing its potential for timesaving and research facilitation but also biased information and the limiting of creativity (Fiialka et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Abu Khurma et al ( 2023) examined ChatGPT's use in UAE education, highlighting its benefits and drawbacks and providing ethical recommendations. Ukrainian higher education also demonstrated the impact of ChatGPT, revealing its potential for timesaving and research facilitation but also biased information and the limiting of creativity (Fiialka et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was found that AI is an integral competent of reforming education in Ukraine and is used to introduce high-quality STEM education (Chmyr & Bhinder, 2023;Kniazkova et al, 2024;Yuskovych-Zhukovska et al, 2022). Fiialka et al (2023) paid the attention towards peculiarities of using ChatGPT in the Ukrainian education. It is worth mentioning that recent findings demonstrate positive impact of AI-based technologies on Ukrainian education for peace and security (Bakhmat et al, 2024;Matviichuk et al, 2024).…”
Section: Personalized Learningmentioning
confidence: 99%
“…The ability of ChatGPT to provide fast, correct, and high-quality code solutions is also reported (Logozar, 2023). Meanwhile, several limitations to using ChatGPT in programming are observed, including potential biases and the inability of ChatGPT to process visual information; privacy and security issues when exposing students' information to ChatGPT during their interactions; and misuse of ChatGPT by obtaining ready solutions without understanding (Fiialka et al, 2023;Rahman & Watanobe, 2023). Megahed et al (2023) found that ChatGPT may generate incorrect programming codes and cannot accurately detect and resolve programming errors.…”
Section: Background and Literaturementioning
confidence: 99%